Novel and simple technique for interfacial shear strength of liquid-solid compound casting specimen. (2021) - Ayadi, Badreddine; Ramadan, Mohamed
Abstract: A novel testing technique for the interfacial shear strength of the liquid-solid compound casting specimen was designed. Two different bimetallic materials specimens were fabricated and subsequent cut for interfacial shear testing. To ensure the easy cutting and testing of bimetallic specimen, two kinds of bearing materials were cast into metallic mold contain two different ferrous solid substrates. Direct tinning process using a mixture of tin powder and flux was applied on the solid substrates before pouring the liquid metal. In current novel testing technique, a minimum cutting and machining processing on the bimetal casting specimen were applied to minimize the internal stresses resulted from multi steps of cutting and machining processes that used in other interfacial shear strength testing techniques. Other previously used shear strength testing technique for bimetal materials was used for a comparison with the current technique. The present shear test technique offers simple and convenient approach for preparing and testing the bimetallic specimens.